Simulating Solitary Wave Generation Using Incompressible SPH - Asghar Farhadi (Annals of Limnology and Oceanography - Peertechz Publications, 2016)
The current study examines the generation and propagation of a Third order solitary water wave along the channel. Surface displacement and wave profi le prediction challenges are interesting subjects in the fi eld of marine engineering and many researchers have tried to investigate these parameters. To study the wave propagation problem, here, fi rstly the meshless Incompressible Smoothed Particle ydrodynamics (ISPH) numerical method is described. Secondly, the boundary condition handling method, discretization, timestep selection and geometry provitions are presented. The numerical model is then used to simulatesolitary wave propagation along the fi xed depth channel. Here two still water depths of h = 0.2 m and h= 0.3 m are assumed and the dimensionless height of desired wave ranging from  = 0.1 to = 0.6 are simulated. The numerical results show that studied Grimshaw Third order method can track the wave profi le and it has acceptable relative variation for 5 seconds after the wave propagation, about 10%. In general, the numerical model gives satisfactory results for the wave kinematics.